The Flexor Tendons in the didelphid manus - Abdala, Virginia Sara Luz (2006)
Tetrapods have flexor tendons in the palmar surface of the manus that transmitforces generated by superficial and deep forearm muscles to the digits. Two patterns (“P”and “L”) of tendinous connections among the deep layer of the forearm muscles and the digitshave been described, one of which (pattern P) shows an empirical correlation with somegrade of arboreality. In this article, we focused on the anatomical design of the tendons ofthe deep layer of the palmar surface of the didelphid manus, and associated muscles. Ourobjectives are: (1) to describe the pattern found in all taxa of the great didelphid clade, (2)to assign the designs that we found to the L or P pattern, and (3) to discuss our results inthe context of the latest available phylogenetic hypotheses proposed for those taxa. All ofthe didelphids we dissected possess the P pattern. As we compared the tendinous andmyological structures, we found that some of the myological differences we describe couldhave important phylogenetic implications. We selected 10 characters, mapped them on mar-supial phylogenies, and discovered six more synapomorphies supporting clades alreadyproposed by other researchers.